Learning from CLT-Informed Interactive Video: Cognitive Performance and Learning Motivation in Culinary Education - Mauren Gita Miranti; Nona Rachel Putri Talaperu; Lucia Tri Pangesthi; Hanif Naufal Ahmi; Anderson Ngelambong (International Journal of Pedagogy and Teacher Education, 2026)
Grounded in Cognitive Load Theory (CLT), this study examined whether CLT-informed interactive video instruction was associated with improvements in students’ cognitive performance and learning motivation in vocational culinary education. A one-group pretest–posttest design was employed involving 41 eleventh-grade culinary arts students at a public vocational high school in East Java, Indonesia. Data were collected using a 30-item cognitive test and a 35-item learning motivation questionnaire, both of which demonstrated acceptable content validity and high internal consistency (α = 0.914 and α = 0.866, respectively). Because some variables did not meet normality assumptions, non-parametric analyses were used. Wilcoxon signed-rank tests were conducted to examine pre–post changes in cognitive performance and learning motivation, while Spearman’s rho was used to examine the relationship between post-intervention learning motivation and cognitive performance gain. The results showed statistically significant improvements in both cognitive performance (Z = −3.650, p < .001) and learning motivation (Z = −2.130, p = .033) following the intervention. However, no statistically significant relationship was found between learning motivation and cognitive performance (rs = −.188, p = .319). These findings suggest that CLT-informed interactive video may serve as a promising instructional medium for improving topic-specific cognitive performance and supporting learning motivation in vocational culinary education.